The Responsibility to Protect in a world of already existing intervention. (December 2019) - Dunford, Robin; Neu, Michael
In the face of humanitarian crises, members of the international community are often presented with a choice: engage in forms of action, including military intervention, or stand by and watch. This framing ignores practices of intervention that are already taking place and contributing to the emergence and perpetuation of humanitarian crises. Despite calling for more attention to be paid to already existing intervention, literature on the Responsibility to Protect has not adequately understood its implications for the legitimacy and likely effectiveness of military intervention. To redress this gap, we argue, first, that a focus on already existing intervention complicates the moral calculus on which defences of military intervention as part of the Responsibility to Protect are based. Second, we claim that actors already engaged in damaging practices of intervention are bad international citizens who are not fit for the purpose of humanitarian military intervention. Third, we argue that in both ignoring already existing intervention and calling for additional military intervention under its third pillar, the Responsibility to Protect legitimises a moralistic form of militarism. These three arguments show that it is a mistake to follow recent literature in responding to already existing intervention by simply adding to the Responsibility to Protect, for instance, duties to engage in structural prevention and to support refugees. Rather, what is needed is a more fundamental rethink that departs from the Responsibility to Protect.